A study on the introduction of the speed warning device / Hassanudin Sudharmin - Sudharmin, Hassanudin (1986)
This study shows that the situation of road accidents in this country is becoming from bad to worse. With regards to the Peninsular Malaysia, the increasing trend in road accidents each year is the factor whi.ch leads the Government to consider adopting a measure to, at least, reduce the increasing number of road accidents. Bearing that in mind, the Speed Warning Device was introduced and the Speed Warning Device Rules, 1985 was implemented on the 1st of January 1986. The main objective of the Government to draw up such rules was to help to reduce or prevent road accidents. However, several problems were encountered by the authority and vehicle operators due to the implementation of the rules. Studies have shown that the offence of exceeding speed limits is only regarded as an offence if the offender is detected and some parties were even trying to manipulate and foil the implementation of the rules. It was also found that certain parts of the Road Traffic Ordinance, 1958 need to be reviewed. It is hoped that once recommended, the Road Traffic Ordinance, 1958 will help to increase the efficiency or traffic regulations in this country. Together with some recommendations, it is also hoped that the recommendations should be able to solve the current problems encountered.